Vitamins and Hormones : advances in research and applications - Marrian, G. F.; Harris, Robert S.; Thimann, Kenneth V. (Academic Press, London, 1959)
Annotation First published in 1943, Vitamins and Hormones is the longest-running serial published by Academic Press. In the early days of the Serial, the subjects of vitamins and hormones were quite distinct. Now, new discoveries have proved that several of the vitamins function as hormones and many of the substances inferred by the title of the Serial function in signal transduction processes. Accordingly, the Editor-in-Chief has expanded the scope of the serial to reflect this newer understanding of function-structure relationships in cellular communication. The Editorial Board now reflects expertise in the field of hormone action, vitamin action, X-ray crystal structure, physiology and enzyme mechanisms. Under the capable and qualified editorial leadership of Dr. Gerald Litwack, Vitamins and Hormones continues to publish cutting-edge reviews of interest to endocrinologists, biochemists, nutritionists, pharmacologists, cell biologists, and molecular biologists. This 54th volume of Vitamins and Hormones includes reviews that deal with gene regulation and signal transduction relating to nutrition, insulin action, and the steroid receptor gene family. The contributors include leading international authorities.
Library has lacks v. 1, v. 3, v. 4, v. 5, v. 6, v. 8, v. 12, v. 13, v. 14, v. 15, v. 16. Library has v. 2, v. 7, v. 9, v. 10, v. 11, v. 17.
Includes bibliographical references and index.
Scholarly & Professional
Keywords: Vitamin -- Hormone